Spatial proteomics identifies a spectrum of immune dysregulation in acquired bone marrow failure syndromes - Koldej, Rachel M.; Prabahran, Ashvind; Tan, Chin Wee; Ludford-Menting, Mandy; Morgan, Huw; Holzwart, Nicholas; Davis, Melissa J.; Ritchie, David S. (Frontiers in Immunology, 2023)
Poor Graft Function (PGF), manifested by multilineage cytopenias and complete donor chimerism post allogeneic stem cell transplantation (alloSCT), and acquired Aplastic Anaemia (AA) are immune mediated acquired bone marrow (BM) failure syndromes with a similar clinical presentation. In this study, we used spatial proteomics to compare the immunobiology of the BM microenvironment and identify common mechanisms of immune dysregulation in these conditions. Archival BM trephines from patients exhibited downregulation of the immunoregulatory protein VISTA and the M2 macrophage marker and suppressor of T cell activation, ARG1 with increased expression of the immune checkpoint B7-H3 compared to normal controls. Increased CD163 and CD14 expression suggested monocyte/macrophage skewing which, combined with dysregulation of STING and VISTA, are indicative of an environment of reduced immunoregulation resulting in the profound suppression of hematopoiesis in these 2 conditions. There were no changes in the immune microenvironment between paired diagnostic AA and secondary MDS/AML samples suggesting that leukaemic clones develop in the impaired immune microenvironment of AA without the need for further alterations. Of the 8 proteins with dysregulated expression shared by diagnostic AA and PGF, the diagnostic AA samples had a greater fold change in expression than PGF suggesting that these diseases represent a spectrum of immune dysregulation. Unexpectedly, analysis of samples from patients with good graft function post alloSCT demonstrated significant changes in the immune microenvironment compared to normal controls, with downregulation of CD44, STING, VISTA and ARG1 suggesting that recovery of multilineage haematopoiesis post alloSCT does not reflect recovery of immune function and may prime patients for the development PGF upon further inflammatory insult. The demonstrable similarities in the immunopathology of AA and PGF will allow the design of clinical interventions that include both patient cohorts to accelerate therapeutic discovery and translation.